On-farm Evaluation and Demonstration of Koekoek chicken under farmers condition in North western Tigray, Ethiopia - Teklemariam Abadi; Desale Gebretsadik; Kibrom Gebremedhin; Teklehaimanot Tsigab; Mulalem Zenebe; Daniel Desta (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
The demonstration trail was conducted at Tselemti district northwestern zone of Tigray. Main objective of the study was to compare production performance of the Koekoek chicken. A total of 60 female headed households were included in the study. Twenty Koekoek chicks forty-five days old were delivered to each participant farmers. Quantitative data such as age at first laying, average weight of male and female chicken, average weight of eggs, average number of egg laying per year of the chicken and qualitative data farmers point of view was collected. The collected data was analyzed using the descriptive statistics such as mean and percentage. Based on the result, the average weight for male and female Koekoek were recorded 2.65 kg and 1.82 kg, respectively. While the local chickens were gave an average weight of 2.01kg and 1.3 kg both male and female, at twelve months age, respectively. The breeds produce an average egg production of 176.03 and 81.4 hen-1year-1, respectively both the Koekoek and local. The result from farmers response shows, the breeds are promising in most of the attributes such as, age to egg laying and slaughter, egg laying capacity, hatchability and market price of the egg as compared to the local. But farmers raised that the breeds are poor in brooding, resistant to diseases, in escaping from predators and low market preference of the chicken than the local. By giving strong emphasis on the management aspect like housing, vaccination and feeding, the breed is promising to the area.